Efficacy and adverse events of immune checkpoint inhibitors: evidence from non-small cell lung cancer and gastric cancer in Korea and Japan - Mc Neil Valencia; Zeeshan Abbas; Seung Won Lee (Precision and Future Medicine)
In recent years, immune checkpoint inhibitors (ICIs) have changed the landscape of cancer treatment by harnessing their efficacy in treating malignancies. These cancer therapies have shown remarkable result and efficacy across multiple cancer types. However, this review specifically focuses on non-small cell lung cancer (NSCLC) and gastric cancer (GC) due to their high incidence rates in Korea and Japan, ranking first to second in both sexes, as well as the availability of real-world data assessing ICI efficacy in these populations. In NSCLC, ICI treatment demonstrated better objective response rate and disease control rate, with overall survival (OS) ranging from 8.4 to 12.6 months in different studies. Nivolumab and atezolizumab exhibited efficacy in disease management in lung lesions. In GC, ICI showed promising efficacy in biomarker-positive patients, including those with programmed death-ligand 1 positive tumors, human epidermal growth factor receptor 2 (HER2) positive tumors, and microsatellite instability-high/mismatch repair (MSI-H/MMR)-deficient tumors, indicating that ICIs are beneficial for patients with favorable biomarker profiles. The median OS was significantly longer in patients with GC who were treated with ICI (16.9 months vs. 13.9 months). Immunotherapy leads to a durable response and improves the survival rates of patients with advanced or metastatic cancers. However, the success of ICI is affected by mild to severe immune-related adverse events, which are potentially life-threatening. Given the expanding ICIs application across different cancer, further studies are warranted to explores its broader implications and limitations. Therefore, this review explored the impacts of ICIs and their potential drawbacks in cancer treatment in Korea and Japan using real-world data and clinical trials.